Long‐term in situ persistence of biodiversity in tropical sky islands revealed by landscape genomics - Alicia Mastretta‐Yanes; Alexander T. Xue; Alejandra Moreno‐Letelier; Tove H. Jorgensen; Nadir Álvarez; Daniel Piñero; Brent C. Emerson (2017)
Abstract Tropical mountains are areas of high species richness and endemism. Two historical phenomena may have contributed to this: (i) fragmentation and isolation of habitats may have promoted the genetic differentiation of populations and increased the possibility of allopatric divergence and speciation and (ii) the mountain areas may have allowed long‐term population persistence during global climate fluctuations. These two phenomena have been studied using either species occurrence data or estimating species divergence times. However, only few studies have used intraspecific genetic data to analyse the mechanisms by which endemism may emerge at the microevolutionary scale. Here, we use landscape analysis of genomic SNP data sampled from two high‐elevation plant species from an archipelago of tropical sky islands (the Trans‐Mexican Volcanic Belt) to test for population genetic differentiation, synchronous demographic changes and habitat persistence. We show that genetic differentiation can be explained by the degree of glacial habitat connectivity among mountains and that mountains have facilitated the persistence of populations throughout glacial/interglacial cycles. Our results support the ongoing role of tropical mountains as cradles for biodiversity by uncovering cryptic differentiation and limits to gene flow.